Money Demand in a High Inflation Economy: The Case of Israel - Yashiv, Eran (The Review of Economics and Statistics, 1994)
Money demand plays a central role in recent models of rapid inflation and stabilization which are highly relevant to the Israeli economy. This paper uses co-integration analysis to estimate money demand in Israel. We find that money demand shifted at the beginning of the 1980s, probably as a result of increased use of liquid indexed assets which provide protection against high inflation. In the previous two decades the equation was a fairly conventional 'U.S.-type' logarithmic function. In the last decade the equation has had a lower constant and has exhibited less sensitivity to interest rate changes. In both periods the nominal rate of interest and real private consumption have been co-integrated with real M1 balances, and interest elasticity has been less than unity. Copyright 1994 by MIT Press.